2019
DOI: 10.1161/circulationaha.119.041080
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Presentation and Management of Valvular Heart Disease

Abstract: Background: Valvular heart disease (VHD) is an important cause of mortality and morbidity and has been subject to important changes in management. The VHD II survey was designed by the EURObservational Research Programme of the European Society of Cardiology to analyze actual management of VHD and to compare practice with guidelines. Methods: Patients with severe native VHD or previous valvular intervention were enrolled prospectively across 28 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 376 publications
(128 citation statements)
references
References 34 publications
2
115
2
9
Order By: Relevance
“…In this prospective cohort study detailing contemporary therapeutic decision-making and outcomes of elderly patients with severe symptomatic AS in a wide range of centers throughout mainland China, our key findings are as follows: (1) In current clinical practice, the decision against intervention was taken in about one-fifth of elderly patients with symptomatic severe AS, half of which were due to patients' subjective preferences. (2) Reduced LVEF and increased EuroSCORE-II were strongly associated with physicians' decisions to deny intervention, suggesting that surgical risk remained the primary concern for physicians when making therapeutic decisions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this prospective cohort study detailing contemporary therapeutic decision-making and outcomes of elderly patients with severe symptomatic AS in a wide range of centers throughout mainland China, our key findings are as follows: (1) In current clinical practice, the decision against intervention was taken in about one-fifth of elderly patients with symptomatic severe AS, half of which were due to patients' subjective preferences. (2) Reduced LVEF and increased EuroSCORE-II were strongly associated with physicians' decisions to deny intervention, suggesting that surgical risk remained the primary concern for physicians when making therapeutic decisions.…”
Section: Discussionmentioning
confidence: 97%
“…Therapeutic Decision-Making and Outcomes in Elderly Patients With Severe Symptomatic Aortic Stenosis: Prognostic Implications of Elderly Patients' Initial Decisions INTRODUCTION Aortic stenosis (AS) is a common disease in the elderly, and its prevalence continues to rise as the population ages (1,2). There is a general consensus that aortic valve replacement (AVR) should be advised in patients with severe symptomatic AS (3,4).…”
mentioning
confidence: 99%
“…3 However, the diagnosis of AS remains challenging, despite it being the most common valvular heart disease (VHD) in the Western world. 7 Diagnosis of AS needs to be established early when the asymptomatic patient is well, decompensation has not taken place and intervention can be planned. Recent data, however, confirm that diagnosis of AS-affected patients is often missed, 8 and by the time of referral for intervention ~80% have severe symptoms and frequently impaired left ventricular (LV) function.…”
Section: How Might This Impact On Clinical Practice?mentioning
confidence: 99%
“… 3 However, the diagnosis of AS remains challenging, despite it being the most common valvular heart disease (VHD) in the Western world. 7 …”
Section: Introductionmentioning
confidence: 99%
“…The European Society of Cardiology's (ESC) EORP-VHD II registry demonstrated that 24.9% of patients with valvular disease had multiple left-sided lesions. 2 Multi-valve procedures exhibit higher operative mortality than do single valve procedures, with a mortality rate that is double its counterpart. 3 The evaluation of multivalvular disease is di cult due to the misleading hemodynamic interactions of sequential valves on each other.…”
Section: Background and Clinical Relevancementioning
confidence: 99%